Dream in the rhythm: visions of sound and spirit in the MoMa collection - Bonner, Grace Wales; Kuo, Michelle Y.; Liljergen, Dana; Museum of Modern Art (New York, N.Y.) (The Museum of Modern Art, 2023)

The fashion crossroad method: Political and epistemological practices - Costa, Carla; Casarin, Carolina; Júnior, João Dalla Rosa; de Olivera Santos, Heloísa Helena; Medrado, Mi (Sustainability Challenges in the Fashion Industry, 2023)

7 Steps Back/Forward/Aside (Gesturing Towards Decolonial Futures, 2023)

In our hands: Native photography, 1890 to now - Ahlberg Yohe, Jill; Grey Eagle, Jaida; Riley, Casey; Minneapolis Institute of Arts (Minneapolis Institute of Art, 2023)

Semiocapitalismo: Del producto marca, de la mercancía al signo/mercancía - Caro, Antonio (Sb, 2023)

Juan Pablo Echeverri - Echeverri, Juan Pablo (James Fuentes Press, 2023)

Arctic amazon: Networks of global indigeneity - McMaster, Gerald; Vincent, Nina (Goose Lane Editions ; Wapatah Centre for Indigenous Visual Knowledge, 2023)

Meryl McMaster: Nikihci-Âniskotâpân = Bloodline - McMaster, Meryl; Sainte-Marie, Buffy; Halfe, Louise Bernice; Milroy, Sarah; Campbell, Maria; Collection McMichael d'art canadien; Remai Modern; Musée d'art de Joliette; Magenta Publishing for the Arts (The Magenta Foundation, 2023)

Decolonial fashion ethnography: ‘Before yesterday’ method - Medrado, Mi (International Journal of Fashion Studies, 2023)

Decoloniality and fashion: RCDF 10th anniversary - Medrado, Mi (Decolonial Zine on Fashion, 2023)
The Decoloniality and Fashion e-zine celebrates the 10th anniversary of the Research Collective for Decoloniality and Fashion! Please complete this form to receive a FREE copy

Gore aesthetics: Chilean necroliberalism and travesti resistance - Rizki, Cole (Journal of Latin American Cultural Studies, 2023)

Aesthesic and epistemic restitution for the joy of life: Recalling earth, overcoming' the contemporary, knowing otherwise - Vázquez, Rolando (Errant Journal, 2023)